Analisis Faktor-Faktor Yang Mempengaruhi Minat Berkunjung Wisatawan Ke Obyek Wisata Religi Masjid Gedhe Kauman Yogyakarta - Gani Surya Miarsih; Anwani (Journal of Tourism and Economic, 2018)
This study aims to: (1) Determine the influence of objects and tourist attractions on tourists visiting interests in the Kauman Gedhe Mosque in Yogyakarta. (2) Knowing the influence of the facility on tourists visiting interest in the Kauman Gedhe Mosque in Yogyakarta. (3) Knowing the effect of accessibility on tourists visiting interest in the Kauman Gedhe Mosque in Yogyakarta. This research was conducted by collecting data using direct observation and questionnaires to visiting tourists or tourists who had visited the Kauman Gedhe Mosque in Yogyakarta. The sampling technique uses Accidental Sampling, which is a sampling technique based on coincidence, that is, anyone who accidentally meets with a researcher can be used as a sample if the person who happens to be met by the researcher is suitable as a data source. The analysis was carried out with a quantitative approach with statistical analysis of multiple linear regression. Using a 4-point Likert scale measuring instrument. Based on the results of the analysis conducted, it can be seen that tourist objects and attractions have a positive effect on tourists visiting interest, but not significantly. Facilities have a positive and significant influence on tourists visiting interests. Accessibility has a positive effect on tourists visiting interest, but is not significant at 5%. However, if the value of 10%, the accessibility variable has a significant effect on tourists visiting interest in the Kauman Gedhe Mosque in Yogyakarta.